2015
DOI: 10.1016/j.psychres.2015.06.030
|View full text |Cite
|
Sign up to set email alerts
|

The influence of eating psychopathology on autobiographical memory specificity and social problem-solving

Abstract: The primary aim was to examine the role of mood and eating psychopathology on autobiographical memory specificity (AMS) and social problem solving (SPS). A further aim was to establish if AMS mediated the relationship between eating psychopathology and SPS. A non-clinical sample of 52 female undergraduates completed the autobiographical memory test (AMT), where they were asked to retrieve specific memories of events from their past in response to emotional cue words, and the meansend problem-solving task (MEPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 84 publications
1
32
1
Order By: Relevance
“…calculation conducted using G*Power revealed that a sample size of 66 would be required to detect a medium effect size F 2 =0.17 (calculated from Ridout et al, 2015) in a multiple regression with a total of 5 predictors (3 tested and 2 control) with a power of 0.80 and an alpha level of 0.05, which suggests that our study was adequately powered.…”
Section: Participantsmentioning
confidence: 91%
See 3 more Smart Citations
“…calculation conducted using G*Power revealed that a sample size of 66 would be required to detect a medium effect size F 2 =0.17 (calculated from Ridout et al, 2015) in a multiple regression with a total of 5 predictors (3 tested and 2 control) with a power of 0.80 and an alpha level of 0.05, which suggests that our study was adequately powered.…”
Section: Participantsmentioning
confidence: 91%
“…4 Another cognitive function influenced by disordered eating is autobiographical memory (Dalgleish et al, 2003;Ridout et al, 2015), which refers to the retrieval of personal memories about past experiences and events. According to Conway and Pleydell-Pearce (2000), autobiographical knowledge is stored hierarchically with information about general summaries of events referred to as categoric memories (e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…The Means-Ends Problem Solving (MEPS) tests an established procedure that challenges individuals to generate solutions to realistic problem scenarios (Spivack, Platt, & Shure, 1976). Individuals with BED and subclinical disordered eating tend to generate less effective solutions on this task (Ridout, Matharu, Sanders, & Wallis, 2015; Svaldi, Caffier, & Tuschen-Caffier, 2010). Other studies using realistic problem-solving scenarios found that individuals with AN and bulimia nervosa (BN) performed worse on the Anorexia and Bulimia Problem Inventory, with particular weakness in weight and eating related scenarios (Espelage, Quittner, Sherman, & Thompson, 2000; Holt & Espelage, 2002).…”
Section: Introductionmentioning
confidence: 99%